Leverage, Profitability and Firm Size on Dividend Policy: Liquidity as a Moderating Variable in Indonesian Healthcare Sector Companies - Luthfiyyah Nur Rasyidah; Achmad Kautsar (Lavish Opulent Education, 2024)
This research aims to determine the effect of leverage, profitability, and firm size on dividend policy with liquidity as a moderating variable in healthcare sector companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022. This type of research is quantitative research with secondary data sources. The sample in this research was 10 companies from the healthcare sector listed on the Indonesia Stock Exchange (BEI) in 2018-2022. The analysis technique used in this research is Moderated Regression Analysis (MRA) using SPSS 25. The results of this research show that leverage and profitability do not have a significant effect on dividend policy. Firm size has a significant positive effect on dividend policy. Liquidity can weaken the influence of leverage on dividend policy. Liquidity is unable to moderate the influence of profitability on dividend policy. Therefore, the factor that healthcare sector companies need to pay attention to before determining their dividend policy is company size. Large companies need to manage their assets well so that their financial performance will improve. It means that the company is able to obtain large amounts of cash from their assets so that free cash flow increases and they are able to distribute dividends. Furthermore, the company must be able to manage the use of debt and its current assets optimally so that the company's finances will keep stable than they can fulfill its obligations well, including distributing the dividends.